(untitled) (Archives of Criminology, 2023)
The Epilogue begins by describing the ambiguity of the meaning of human trafficking (HT) before offering a review of the 4P’s that represent the primary responses to combatting HT. A brief reference is then made to a ’new’ P - participation – and how it can play an essential role in fighting HT. The article then notes that there remains a dearth of research on forced labour trafficking despite its rich history. A summary of the articles is presented with an emphasis on identifying existing gaps in our knowledge and research. The Epilogue concludes with several vital suggestions for future efforts to combat forced labour trafficking.